2006
DOI: 10.1590/s0103-21002006000300007
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de pessoas com diabetes em unidades de atenção primária e secundária em relação a fatores desencadeantes do pé diabético

Abstract: OBJETIVO: estudo descritivo que caracterizou pessoas com diabetes da rede básica de saúde em relação aos fatores desencadeantes do pé diabético, considerando variáveis socio-demográficas, história clínica e risco para complicações nos pés. MÉTODOS: obtiveram-se dados mediante entrevista e avaliação dos pés. Na análise foi considerada avaliação dermatológica, estrutural, circulatória e neurológica e classificados conforme proposta de Sims e colaboradores. RESULTADOS: a idade média foi 58,5±8,5 anos; tempo da do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
79

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 19 publications
(24 reference statements)
0
8
1
79
Order By: Relevance
“…The risk classification identified that 7.9% presented plantar insensitivity and 6.9% presented plantar insensitivity and foot deformity. The study concluded that such disorders could be prevented through basic education and interventions for foot care, in which external factors identified in this study could be resolved and monitored with actions of low complexity (16) .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The risk classification identified that 7.9% presented plantar insensitivity and 6.9% presented plantar insensitivity and foot deformity. The study concluded that such disorders could be prevented through basic education and interventions for foot care, in which external factors identified in this study could be resolved and monitored with actions of low complexity (16) .…”
Section: Discussionmentioning
confidence: 84%
“…Nurses should take the responsibility to track and monitor risk factors for Diabetic Foot during the care process and instruct people with DM concerning the risks and, with the involvement of the entire health team, determine the basic interventions and plan educational activities for selfcare and maintenance of a good metabolic control in order to avoid severe complications (16) . Hence, this intervention is closely related to the nursing intervention of the diagnosis Ineffective management of therapeutic regimen, considered complementary for identification of risk.…”
Section: Discussionmentioning
confidence: 99%
“…The exposed paresthesia conditions are important parameters for evaluating the nurse in the care process, which allows determining the basic interventions and planning educational activities according to needs of diabetic patients. 18 We concluded that the nurse plays a fundamental role with regard to the care to individuals with lower limb ulcers and plays a key care when dealing with such wounds. This professional monitors the injury, directs and executes the making of dressing efficiently and effectively.…”
Section: Discussionmentioning
confidence: 95%
“…2,[15][16][17] The low level of smoking in the study population is a positive factor, as tobacco consumption constitutes an aggravating to occlude arteries and arterioles, since peripheral atherosclerotic vascular disease is one of diabetic complications and that appears prematurely. 18 The elimination of advertising and of activities that promote tobacco products are meant to reduce the incentives for the initiation and to deconstruct the positive social acceptance of smoking. 19 Sedentarism was evident in the population studied in 71.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos de Hirota et al (2008) e os de Ochoa-Vigo et al (2006) inferem que decorrente dos efeitos deletérios da NP, associados às doenças vasculares periféricas (DVP) tem-se os transtornos tróficos da pele e da estrutura osteoarticular do pé culminando com as úlceras, o pé diabético, representando em 90% dos casos, uma das mais mutilantes complicações crônicas do DM devido ao aumento da suscetibilidade à infecção.…”
Section: Introductionunclassified